Corrigendum - Lanca, Carla (2024)
Publisher Copyright: Copyright © 2024 Lanca, Pang and Grzybowski. Errata de: Lança C, Pang CP, Grzybowski A. Effectiveness of myopia control interventions: a systematic review of 12 randomized control trials published between 2019 and 2021. Frontiers in Public Health. 2023;11:1125000. doi: 10.3389/fpubh.2023.1125000. eCollection 2023.